The 2021 Paycheck Protection Program Reboot - Fairlie, Robert W.,Fossen, Frank M. (National Bureau of Economic Research, 2022)
Was the 278 billion reboot of the 800 billion Paycheck Protection Program (PPP) in early 2021 disbursed equitably to minority communities? This paper provides the first analysis of how PPP funds were disbursed to minority communities in the third and final round of the program, which was specifically targeted to underserved and disadvantaged communities. Using administrative microdata on the universe of PPP loans, we find a strong positive relationship between PPP flows, as measured by the number of loans per employer business or loan amounts per employee, and the minority share of the population or businesses in the third round. In contrast, the relationship was negative in the first round of 2020 and less positive in the second round of 2020. We find a stronger positive relationship between minority share and loan numbers or amounts to employer businesses for first draw loans than second draw loans in 2021 (capturing some persistence in inequities). The patterns are similar for loan numbers and amounts to nonemployer businesses but with a strong positive relationship with minority share for both first draw and second draw loans. The rebooted PPP that ran from January to May 2021 appears to have been disbursed to minority communities as intended
10.3386/w29732
Keywords: Arbeitspapier; Graue Literatur; Coronavirus; Epidemie; Konjunktur; Stabilisierungspolitik; Subvention; KMU; Minderheit; Wirkungsanalyse; USA